2013
DOI: 10.1007/s00296-013-2676-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia induced by adenosine 5′-monophosphate attenuates early stage injury in an acute gouty arthritis rat model

Abstract: To investigate whether the hypothermia induced by Adenosine 5'-Monophosphate (5'-AMP) could attenuate early stage injury in a rat acute gouty arthritis model. Ankle joint injection with monosodium urate monohydrate crystals (MSU crystals) in hypothermia rat model which was induced by 5'-AMP and then observe whether hypothermia induced by 5'-AMP could be effectively inhibit the inflammation on acute gouty arthritis in rats. AMP-induced hypothermia has protective effects on our acute gouty arthritis, which was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Our experiments confirmed that AIH was able to significantly inhibit the NF-κB pathway. This result was consistent with other studies [10,35,36]. In LPS-stimulated inflammatory pathways, JNK signaling is key for cytokine production [37].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our experiments confirmed that AIH was able to significantly inhibit the NF-κB pathway. This result was consistent with other studies [10,35,36]. In LPS-stimulated inflammatory pathways, JNK signaling is key for cytokine production [37].…”
Section: Discussionsupporting
confidence: 94%
“…When administered at a sufficient dose, 5′-AMP allows nonhibernating mammals to rapidly undergo reversible and safe severely hypothermic reactions at ambient temperatures (ATs) of 15-16°C [9][10][11][12][13]. Recently, studies have shown that hypothermia induced by 5′-AMP has an anti-inflammatory effect [10,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Cryoimmersion may have been effective in reducing the presence of exudate in the joint through capillary contraction, making it difficult to release inflammatory factors, such as P, bradykinin and histamine. Therefore, inflammatory suppression is positive because it protects the joint synovial tissue from harmful processes (Miao et al, 2013;Zhang et al, 2018).…”
Section: Figmentioning
confidence: 99%
“…In the Miao et al (2013) study, about the repercussions of hypothermia on gouty arthritis induced by urate crystals on the ankle, adenosine 5¢ monophosphate was used to reduce the central temperature of Wistar rats by 16-18°C for *10 hours. As a consequence, they demonstrated that hypothermia reduced joint edema and leukocyte infiltration of the treated group.…”
Section: Figmentioning
confidence: 99%
“…Another study demonstrated that whole body cooling increased stabilization of a temperature-sensitive Cystic Fibrosis (CF) mutant protein, ΔF508-CFTR, improved its functions, alleviated CF pathological phenotypes and decreased mortality in CF mice [27]. Similar AIHM procedures are now used by independent research groups to cool experimental animals of various disease models [28][29][30][31][32]. …”
Section: Discussionmentioning
confidence: 99%